Convergence Axioms on Dislocated Symmetric Spaces - I. Ramabhadra Sarma; J. Madhusudana Rao; P. Sumati Kumari; D. Panthi (Abstract and Applied Analysis)
Dislocated symmetric spaces are introduced, and implications and nonimplications among various kinds of convergence axioms are derived.